Multiple regression analysis of job satisfaction among employees at ABC factory / Nurul Husna Jamian ... [et al.] - Jamian, Nurul Husna; Mohammad Hamzah, Mohd Hafiz; Wan Abdul Aziz, Wan Noor Hayatie; Azhar, Farah Waheeda (UiTM Press, 2020)
Job satisfaction is a crucial issue for the company to achieve high productivity and reduce employee turnover. If organization can give the workers satisfaction, it is not only increasing image of an organization, but it also increases motivation and productivity of all workers. Employee who satisfied with their job intention to give the best effort to the company and tend to stay long in the factory. Hence, the purpose of this research is to find out the factor that influence job satisfaction among workers at ABC factory. 80 employees at the ABC Factory completed a set of questionnaire consists of two parts, which are background of respondent and job satisfaction components. Multiple Linear Regression is used to analyze the result to achieve the objective stated. The findings revealed that among four independent variables, Work Environment and Organization have significantly effect Job Satisfaction at ABC Factory.